Measurement of facet reflectivity of antireflection-coated electroabsorption modulator using induced photocurrent - Kang, BK; Park, YH; Lee, S; Choi, SS; Lee, J; Kamiya, T; Park, SH (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2001)
A new method to measure the facet reflectivity of an antireflection (AR)-coated electroabsorption (EA) modulator in the region of operating wavelengths is proposed. First, by measuring induced photocurrent and reflectance simultaneously at the front facet of an EA waveguide, the cleaved facet reflectivity and propagation loss are determined. After coating the facet with AR, the residual reflectivity of AR-coated facet is obtained from the measured photocurrent spectra and the predetermined facet reflectivity. We demonstrate the reflectivity of a double- layer AR-coated EA modulator can be measured to be similar to4 X 10(-4) at 1.55 mum for TE polarization by using the proposed technique.
Keywords: AMPLIFIERS